“Maneiras diferentes de trabalhar com a verdade”: a criação visual do universo fictício no documentário que bom te ver viva (1989) de Lúcia Murat - Silva, Jessica Kelly Rodrigues de Andrade (2020)
This research aimed to investigate, through film analysis of the documentary feature Que Bom Te Ver Viva (1989), by Lúcia Murat, possibilities of visual creation of a fictional universe inserted in a documentary film, through the hybridism of characteristics of the two cinematographic genres. Que Bom Te Ver Viva (1989) was the first feature film by the filmmaker from Rio de Janeiro, who is a former member of the armed struggle against the military dictatorship in Brazil, the scenario in which she was severely tortured and in which she spent three and a half years in prison. These facts have a great influence on her film productions, which usually walk the boundaries between fiction and documentary cinema. Lúcia Murat has already won several national and international awards and has more than eleven outstanding productions in her career. For the realization of this research I counted on the resources offered by the bibliographical research that, in the first chapter, contributed to a better location of Murat’s biography. The same research methodology was also used, in the second chapter, to identify characteristics specific to the documentary and fictional genres, as well as their possibility of hybridism, since it is through the resources that the director makes use of the execution of her films. In the third chapter, the methodology used was film analysis, using the use of its processes and resources, I recognized some components used by Lúcia Murat to build the fictional universe of the documentary Que Bom Ver Ver Te Viva. Through the research, it was possible to observe that among the various possibilities of visual creation of a fictional universe in a documentary film, in the 1989 film hybridity is visually manifested through the creation of a fictional character, played by Irene Ravache and all the scenographic elements that she interacts with.